Melatonin influence on clinical and endocrine measures in early rheumatoid arthritis - E. Y. Pogozeva; A E Karateev; D E Karateev; E N Alexandrova; A A Novikov; V A Nasonova (Научно-практическая ревматология)
Objective. To assess melatonin (ML) efficacy for correction of sleep disturbances, its influence on clinical symptoms and laboratory activity measures as well as cortisol level in pts with rheumatoid arthritis (RA) Material and methods. Blind randomized placebo controlled study was performed. 38 women with RA fulfilling ACR criteria and disease duration not exceeding a year were included. Pts of the main group (n=19) received melatonin (Melaxen, Unifarm, USA) 3 mg I hour before sleep, control group pts (n= 19) received placebo. All pts received nonsteroidal anti-inflammatory drugs and disease modifying anti-rheumatic drugs. Clinico-laboratory measures of inflammatory activity, sleepless symptoms score, plasma cortisol and urine 6-sulphotoximelanotonin (6-STM) levels with immuno-enzyme assay were evaluated. Results. To the end of study sleep quality improved and morning stiffness significantly decreased in the main group pts in comparison with placebo group. 20% decrease of morning stiffness was achieved in 90% of ML group and 44% of placebo group pts. Other clinical features of RA including DAS28 changes did not significantly differ between groups. Treatment with ML also induced endocrine status changes in RA pts: decrease of plasma cortisol and significant increase of urine 6-STM levels. Endocrine measures did not change in placebo group. Conclusion. ML efficacy in the treatment of sleep disturbances in pts with RA was confirmed. Decrease of cortisol blood level in such pts probably connected with shift of its peak to earlier hours providing decrease of morning stiffness.